Numerical study on the collision of Platform Supply Vessel and Floating Production Storage and Offloading platform. (3rd July 2022) - Fernandez, Jorge M.; Vaz, Murilo A.; Cyrino, Julio C. R.
ABSTRACT: The first Floating Production Storage and Offloading platforms (FPSOs), many still operating in Campos Basin, were converted from single-hull oil tankers. Therefore, collision leading to the FPSO side plating fracture is a serious concern. To simplify the numerical simulation of collision a Platform Supply Vessel (PSV) is modelled assuming a perfectly rigid bow structure, which can deem excessively conservative assessment. Therefore, the objective of this paper is to evaluate the actual expected collision damage considering a deformable PSV bow structure. In this investigation, the resistance of a single-hull FPSO side structure is studied for two collision scenarios, considering the PSV bow rigid and deformable and employing RTCL and plastic strain fracture criteria. It is shown that the conservative combination of equivalent plastic strain criterion and rigid bow may overestimate the damage severity, while the consideration of deformable PSV bow and RTCL criterion does not lead to a single-hull FPSO fracture for the collision scenarios investigated.